Improving Learning Outcomes by Using Think Pair Share (TPS) Cooperative Learning Model at Primary School Students - Zuddin, Mufari (JPI (Jurnal Pendidikan Indonesia), 2018)
This classroom action research was conducted to improve the learning outcomes of Civics by applying the cooperative model of Think Pair Share (TPS) type on V grade students that consists of 24 students. Improving PKN learning outcomes by applying cooperative learning model Think Pair Share (TPS). Factors that led to the improvement of Civics learning outcomes with the application of Think Pair Share (TPS) Student Class V SDN 003 Bangkinang. The research subjects of Grade V students are 24 students. The result of the research is the improvement of learning result before the action is done to cycle I and II. Before the students' learning outcomes were classified as "Low" with a percentage of 41.7%, there was an increase in cycle I with a percentage of 62.5% "High". While the students' learning outcomes in cycle II an increase with the percentage of 91.7% "Very High", evidenced by the application of Think Pair Share (TPS) can improve the learning outcomes of Civics Student Class V SDN 003 Bangkinang. It can be seen from the increasing student activity in the learning process by applying Think Pair Share (TPS). then it can be with the application of Think Pair Share (TPS) can increase student learning outcomes of grade V SD 003 Bangkinang.